Using Information and Communication Technologies in Tanzania: responses of information professionals - Nawe, Julita (SAGE Publications, 2000)
Highlights efforts made by information professionals of academic and research institutions in Tanzania in taking advantages of ICTs in supporting of spearheading of knowledge in their respective institutions and the country in general. The study is limited to University of Dar es Salaam and its two campuses, Sokoine University of Agriculture, Institute of Finance Management, and Economic and Social Research Foundation.
Full text can be accessed at http://idv.sagepub.com/content/16/1/24.short